2019
DOI: 10.1590/1981-863720190005820190018
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and clinical behavior on antiresorptive medications and osteonecrosis of the jaws: a cross-sectional study

Abstract: Objective: This present study assessed the knowledge and clinical behaviors of dentists on antiresorptive medications (AM) and osteonecrosis of the jaws (ONJ). Methods: A cross-sectional study was performed by a questionnaire applied to a sample of 101 dentists. It inquired about general information, knowledge on AM and ONJ, behaviors regarding clinical cases of patients, and knowledge acquisition sources. Kappa coefficient (ƙ) checked the questionnaire’s reliability. Descriptive statistics were computed, Fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The results corroborate those found in this study, demonstrating that most professionals ask in the anamneses of all patients which medications they are using, before performing any procedure (94.7%). Although it is unanimous on the part of dentists in the present study and those of Marliére et al [28] that it is extremely important to know during anamnesis which medications are under use by patient, and it will not be useful to know that the patient uses one of the Zometa group, for example, if the dentist is not aware that this is an antiresorptive drug and that, as such, it can cause maxillary osteonecrosis for those who use this medication.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The results corroborate those found in this study, demonstrating that most professionals ask in the anamneses of all patients which medications they are using, before performing any procedure (94.7%). Although it is unanimous on the part of dentists in the present study and those of Marliére et al [28] that it is extremely important to know during anamnesis which medications are under use by patient, and it will not be useful to know that the patient uses one of the Zometa group, for example, if the dentist is not aware that this is an antiresorptive drug and that, as such, it can cause maxillary osteonecrosis for those who use this medication.…”
Section: Discussionmentioning
confidence: 73%
“…Marliére et al [28] carried out a cross-sectional study using a questionnaire applied to a sample of 101 dentists, whose aim was to assess the knowledge and clinical conduct of these professionals regarding antiresorptive drugs and osteonecrosis of the jaws. When asked whether they asked in the anamnesis of all patients which medications they were using before performing any procedure, 83% of dentists reported that it was important to know during anamnesis whether the patient was under the use of antiresorptive drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations